A promising type-II β-AsP/g-C6N6 van der Waals heterostructure photocatalyst for water splitting: a first-principles study. Issue 40 (7th October 2022) - Zhao, Huiyan; Jia, Baonan; Guan, Xiaoning; Chen, Yingjie; Zhu, Xiaoling; Han, Lihong; Lu, Pengfei
Abstract : This work predicts the type-II AsP/g-C6 N6 van der Waals heterostructure as a promising photocatalyst for water splitting, which has better photocatalyst performances compared with the g-C6 N6 monolayer. Abstract : Photocatalytic water splitting, which can use abundant and clean solar energy, is friendly to the environment and consumes less energy. This work predicts the type-II β-AsP/g-C6 N6 van der Waals (vdW) heterostructure as a promising photocatalyst for water splitting using first-principles calculations. Compared with the g-C6 N6 monolayer, the β-AsP/g-C6 N6 heterostructure not only can effectively separate photogenerated electron and hole pairs but also shows considerable light absorption and better photocatalyst performances. The optical absorption coefficient of the β-AsP/g-C6 N6 heterostructure has also extremely increased, more than ten times that of the g-C6 N6 monolayer. The β-AsP/g-C6 N6 heterostructure with little compression (−2%) could be conducive to the hydrogen evolution reaction with a Gibbs free energy closer to zero (−0.46 eV) compared to monolayers. The oxygen evolution reaction has a low theoretical overpotential of 0.63 V. These results indicate that it exhibits favorable performances as a photocatalyst. This work predicts the possible application of the β-AsP/g-C6 N6 heterostructure as a photocatalyst and expands the scope of renewable energy devices.